Big data: human resources management and the right to information of workers’ representatives - Bernal Santamaría, Francisca (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In this article the challenges by the Digital Age are exposed, and specifically, the “Data Age” together with the affectation of fundamental rights, such as the right to data protection of candidates and workers. This challenge analyses Regulation 2016/679 on the protection of natural persons with regard to the processing of personal data and the free movement of this data and its projection in labour relations. Therefore, the algorithm that generates the volume of data available to companies must be known by workers’ representatives as an integral part of their information rights.